Attitudes Toward Entrepreneurship Education, Post-pandemic Entrepreneurial Environment, and Entrepreneurial Self-Efficacy Among University Students - Zhang, Jiping; Huang, Jianhao; Hong, Yao (Frontiers in Psychology, 2022)
Currently, little is known about the mechanism of how university students’ attitudes towards entrepreneurship education affect entrepreneurial self-efficacy in the post-pandemic entrepreneurial environment. Based on the existing research, this study explores the relationship between attitudes towards entrepreneurship education, the post-pandemic entrepreneurship environment and entrepreneurial self-efficacy through a questionnaire survey. A total of 910 university students from three universities in Zhejiang Province, China participated, with an effective rate of 92. 9%. The data collection focused on the period from August to December 2020. In this study, Stepwise Multiple regression analysis was used to analyze university students' attitudes towards entrepreneurship education and its impact on entrepreneurial self-efficacy, as well as the moderating effect of the post-pandemic entrepreneurial environment. The results show that the gender of university students and the entrepreneurial experience of their family members exist significant differences in their attitudes towards entrepreneurship education and also on their entrepreneurial self-efficacy. Furthermore, attitudes towards entrepreneurship education exert a significant and positive impact on their entrepreneurial self-efficacy, while the post-pandemic entrepreneurial environment plays a positively moderating role in this influential process.